Enhanced cycling time-trial performance during multiday exercise with higher-pressure compression garment wear - Williams, E. R.; McKendry, J.; Morgan, P. T.; Breen, L. (International Journal of Sports Physiology and Performance, 2021)
Purpose: Compression garments are widely used as a tool to accelerate recovery from intense exercise and have also gained traction as a performance aid, particularly during periods of limited recovery. This study tested the hypothesis that increased pressure levels applied via high-pressure compression garments would enhance "multiday" exercise performance. Methods: A single-blind crossover design, incorporating 3 experimental conditions—loose-fitting gym attire (CON), low-compression (LC), and high-compression (HC) garments—was adopted. A total of 10 trained male cyclists reported to the laboratory on 6 occasions, collated into 3 blocks of 2 consecutive visits. Each "block" consisted of 3 parts, an initial high-intensity protocol, a 24-hour period of controlled rest while wearing the applied condition/garment (CON, LC, and HC), and a subsequent 8-km cycling time trial, while wearing the respective garment. Subjective discomfort questionnaires and blood pressure were assessed prior to each exercise bout. Power output, oxygen consumption, and heart rate were continuously measured throughout exercise, with plasma lactate, creatine kinase, and myoglobin concentrations assessed at baseline and the end of exercise, as well as 30 and 60 minutes postexercise. Results: Time-trial performance was significantly improved during HC compared with both CON and LC (HC = 277 [83], CON = 266 [89], and LC = 265 [77] W; P < .05). In addition, plasma lactate was significantly lower at 30 and 60 minutes postexercise on day 1 in HC compared with CON. No significant differences were observed for oxygen consumption, heart rate, creatine kinase, or subjective markers of discomfort. Conclusion: The pressure levels exerted via lower-limb compression garments influence their effectiveness for cycling performance, particularly in the face of limited recovery.